Economic load dispatch problem using spider monkey optimisation algorithm. (26th September 2022) - Sharma, Ajay; Sharma, Harish; Bhargava, Annapurna; Sharma, Nirmala
The coal reserves are lessening, and subsequently fuel prices are escalating now a days. Therefore, an appropriate schedule of generating units for thermal energy is indispensable to convince this rising load demand at minimum price by reducing generation cost is termed as economic load dispatch problem (ELDP). Spider monkey optimisation algorithm (SMOA) is implied to execute ELDP. The proposed methodology considers transmission losses, prohibited operating zones (POZs), and multiple fuels constraints (MFCs). The experiments were executed over a variety of arrangements of a different number of generating units. The significance of the applied strategy to solve ELDP is analysed while assessing the reported results with other renowned methods.